In-flight incapacitation and cystic medial necrosis - Truska, Oldrich; Sokol, Milos (Aviation, space, and environmental medicine, 2013)
INTRODUCTION: The major causes of in-flight fatal incapacitation in civil pilots are acute coronary events, new onset idiopathic epilepsy, and physiological problems. Less than 1% of all air accidents are due to sudden incapacitaion. The problem with acute coronary disease is very serious when occurring during critical stages of the flight, such as takeoff or landing, rather than during the cruising phase. CASE REPORT: The authors describe the fatal in-flight incapacitation in a Czech airline captain during the approach for landing. In this case, the first officer tried to communicate with the captain, but there was no response and first aid was unsuccessful. The post-mortem examination showed the cause of the sudden death to be an aortic dissection with cardiac tamponade due to cystic medial necrosis (Erdheim disease). The authors describe the clinical and histological features of Erdheim disease. DISCUSSION: The normal aorta contains collagen, elastin, and smooth muscle cells that form the vessel wall. Degenerative changes lead to breakdown of the collagen, elastin, and smooth muscle, and an increase in basophillic ground substance with the formation of cysts and accumulation of mucopolysaccharide. Medical incapacitation in the cockpit is rare. The leading causes of fatal in-flight incapacitation are myocardial infarction, cardiac arrhythmias, and epileptic seizures; cystic medial necrosis is very rare and no similar cases were found in the aviation literature.
Keywords: ruptura aorty; Humans; lidé středního věku; Aortic Aneurysm, Thoracic; Aerospace Medicine; Aortic Dissection; náhlá smrt; lidé; cysty; Male; Middle Aged; Aortic Rupture; aneurysma hrudní aorty; disekce aorty; Cysts; letecké a kosmické lékařství; mužské pohlaví; Cardiac Tamponade; Death, Sudden; srdeční tamponáda